Simultaneous Identification of Both MFSD8 and RDH12 Pathogenic Variants in a Chinese Family Affected With Retinitis Pigmentosa - Wang, Yihui; Teng, Yanling; Liang, Desheng; Li, Zhuo; Wu, Lingqian (Frontiers in Genetics, 2021)
Retinitis Pigmentosa (RP) is characterized by tremendous genetic and phenotypic heterogeneity. Here, we investigate pathogeny of RP family further in order to provide evidence for the genetic and reproductive counseling of families. While the pregnant woman of 8+3 weeks presented with RP, her first-born with retinitis pigmentosa, epilepsy and cerebellar atrophy. The research identified a compound heterozygous mutation c.998+3_998+6del in MFSD8 of the first-born, explains the cause of proband which cannot explain the mother’s disease. Then a homozygous mutation c.343+1G>A in RDH12 of the mother was found. RT-PCR is employed to find that there is a skipping of exon 10 in MFSD8 and a 15-nucleotide retention of intron5 in RDH12. The coexistence of two independent RP caused by distinct genes in one pedigree is demonstrated. Based on the diagnosis, a prenatal diagnosis performed on the fetus found that the fetus MFSD8 is affected by the same mutation as the proband. The research underscoring the complexity of RP and the need for the combination of extensive molecular genetic testing and clinical characterization, in addition, expands the spectrum of MFSD8 mutations. Finally, it is expected that the family members would be prevented from reproducing children of the similar disease.